Formation Rules for Indonesian Nouns Reduplication (Generative Morphology Review) - Kaharuddin; M. Dalyan; Abbas, Asriani; Hasjim, Munira; Armin, Mardi Adi (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
Morphology is a branch of linguistics that deals with the internal structure of words, and how it formed. This branch of linguistics has a very wide reach so that many aspects can be traced to obtain accurate information. Among these aspects is the aspect of forming Indonesian nouns. Although this aspect has been researched, there is still room for more interesting research. The aspect of formation of Indonesian nouns can still be further investigated by looking at a more specific aspect, namely the rules for forming reduplication nouns using a generative morphology review. This research aims to describe: (1) The process of forming Indonesian reduplicated nouns, (2) The rules for forming Indonesian reduplicated nouns, (3) The morphological and morphophonemic processes that occur in the formation of Indonesian reduplicated nouns, and (4) the original representation and birth representation in the formation of Indonesian reduplication nouns. So, this research attempts to formulate rules for forming reduplication nouns without being designed using statistical procedures. Therefore, this research used qualitative method. The population of this research is the competence of native Indonesian speakers as a whole. The analysis is carried out with a structured work step, which starts with identifying all duplicate Indonesian nouns. The identified reduplication nouns are then classified. The next work step is to formulate a set of rules for forming reduplication nouns. Through the results of the formulation, the original representation is obtained. After the initial representation has gone through a morphological or morphophonemic process as a filter, it arrives at the birth representation. The results of this research show that not all processes of forming reduplication nouns have to go through a filter. Reduplicated nouns that must pass through the filter are only those that are repeated in their entirety. This noun repeated in its entirety expresses the meaning of 'a lot of X'. The reduplication nouns that are not repeated in full must go through a filter to arrive at an acceptable form of reduplication nouns. The filter can be a morphomorphic process or a morphological process. In terms of meaning, apart from showing a plural meaning, there are also reduplication noun constructions that show a single meaning even though they have gone through a reduplication process.